Innovative Business Models for Design Service Providers: Enhancing MSME Digital Transformation - Fathiya Putri Zahra; Suharto, Yulianto (Integrasi Sains Media, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are supported by the Indonesian government to grow through digital transformation as one of the biggest players in the Indonesian economy. Unfortunately, many MSMEs struggle to grow optimally due to the uneven distribution of information and education on business and digital transformation. Design service providers aim to help MSMEs maximize their potential through effective branding and digital marketing. However, even a design service provider encounters challenges, including inefficiencies in the business model and a lack of customer acquisition and retention. This research aims to provide insights and recommendations for business model innovation by evaluating the current business model of a design service provider and developing strategies aligned with current industry conditions. Using the Business Model Framework by Chu and Ten Types of Innovation by Doblin, the study identifies areas that should be evaluated, improved, and innovated. The methodology includes (1) a focus group discussion with the internal team of a design service provider to uncover issues from an internal perspective and (2) interviews with the customer persona of the design service provider, which includes ten potential and past customers, to understand external perspectives. The data is analyzed using thematic analysis, open coding, and pattern coding, followed by triangulation to ensure validity. The findings suggest that existing business models may not meet customer needs and desires. Additionally, MSMEs' varying levels of technology understanding influence their purchasing decisions for design services. Therefore, continuous evaluation and improvement of business models are essential to meet the target market's needs. Design service providers will also need to understand the diverse types of MSMEs to tailor their offerings effectively.